Effect of Pedestal Temperature on Bonding Strength and Deformation Characteristics for 5N Copper Wire Bonding - Singh, G.; Haseeb, A.S. Md. Abdul (Institute of Electrical and Electronics Engineers (IEEE), 2016)
In recent years, copper has increasingly been used to replace gold to create wire-bonded interconnections in microelectronics. While engineers and researchers in the semiconductor packaging field are continuously working on this transition from gold to copper wires to reduce costs, the challenge remains in producing robust and reliable joints for semiconductor devices. This research paper investigates the effect of pedestal temperature on bonding strength and deformation for 99.999% purity (5N) copper wire bonding on nickel-palladium-gold (NiPdAu) bond pads. With increasing pedestal temperature, significant thinning of the copper ball bond can be achieved, resulting in higher as-bonded ball shear strengths while producing no pad damage. This can be helpful for low-k devices with thin structures, so as to prevent the use of excessive bond force and ultrasonic energy during copper wire bonding.